Performance Analysis of Three-Phase Power Flow Algorithms in Power Distribution Networks - Girardi, Mateus F. [UNESP] (2021)
In this paper, it is analyzed two algorithms to calculate the three-phase power flow in electricity distribution networks. The algorithm should be able to present an effective convergence to unbalanced networks spending reduced processing time. The computational analysis assumes the steady state and the behavior of the components present in the electricity distribution network, such as buses with distributed generation and controlled voltage. The performance of the power flow solution is analyzed using one sweep method, called backward/forward sweep power flow that admittedly can maintain a high speed of execution necessary to real-time applications in automation tools of the distribution system. Another solution method is a current injection algorithm based on the Gauss' method using the nodal impedance matrix of the distribution networks to solve the state variables including the voltage profiles in buses and the current flows in lines. The tests are performed through the computational implementation of these two power flow solution algorithms by evaluating comparatively the results obtained from the electrical quantities of the distribution network plus the computational cost.